Berhaji di masa kolonial - Majid, Dien (Jakarta : Sejahtera, 2008)
Muslim pilgrims and pilgrimages to Mecca during Dutch colonial in Indonesia.
Includes bibliographical references (p. 175-182) and index.
Keywords: Muslim pilgrims and pilgrimages -- Indonesia; Muslim pilgrims and pilgrimages -- Saudi Arabia -- Mecca; Indonesia -- History -- 1798-1942.